2020
DOI: 10.18203/2320-1770.ijrcog20200911
|View full text |Cite
|
Sign up to set email alerts
|

Study of early perinatal outcome in lower segment caesarean section in severe foetal distress at tertiary care centre

Abstract: Background: For asphyxia, the fetus reacts with a series of responses. First there is redistribution of blood flow to vital centres to limit the deleterious effects of oxygen limitation in the brain, heart and adrenal glands. A further compensatory response is that overall fetal oxygen consumption declines to values as low as 50% of the control.Methods: This was a prospective study. Early perinatal outcome of newborns delivered through Caesarean section due to clinical foetal distress in labour was compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Indication (NRFHR) of this study shows that it significantly affected the first-minute Apgar score (OR: 4.2, 95% CI: 1.1–17, p = 0.04), which was a similar finding reported by Chandra Kant et al, 39 but the contrary finding was reported from a study done in Tanzania. 35 This controversial report may be the result of the heterogeneity of factors that contribute to NRFHR in the uterus; some factors, such as uterine hyperstimulation and aortocaval compression, cause reversible NRFHR, which is transient and does not affect the first-minute Apgar score.…”
Section: Discussionsupporting
confidence: 72%
“…Indication (NRFHR) of this study shows that it significantly affected the first-minute Apgar score (OR: 4.2, 95% CI: 1.1–17, p = 0.04), which was a similar finding reported by Chandra Kant et al, 39 but the contrary finding was reported from a study done in Tanzania. 35 This controversial report may be the result of the heterogeneity of factors that contribute to NRFHR in the uterus; some factors, such as uterine hyperstimulation and aortocaval compression, cause reversible NRFHR, which is transient and does not affect the first-minute Apgar score.…”
Section: Discussionsupporting
confidence: 72%